مسلکی بنیاد پر فتوی اہل علم کی نظر میں :ایک تحقیقی جائزہ: Fatwa on religious basis in the consideration of scholars: A research analysis - Javed Ali; Dr. Sami ul Haq (Al Manhal Research Journal, 2024)
Fatwa is a fundamental thing in Islamic sharia.this is a satisfactory answer to the upcoming problems but the scholars differ in giving fatwas.There are two types of opinions among the thinkers of islam regarding religiously based fatwas one group claims that the four Masaliks have been codified,so fatwa should be given according to these masaliks and should not gets out of these masaliks and should adopt one of these masaliks so that it is not acted on the basis of selfish desires,because many scholars may disagree on an issue, then once the justification of the issue will be followed and a fatwa will be given.And the scond time on the illegal,that is ,once there will be a fatwa and action on the opinion of a scholar, and the second time the opinio of another scholar will be accepted, then the religion will be subordinated to desires, therefor,a ftwa should be given on a religious basis and not on the basis of self desirs. Some of the scholars are convinced of strictness,but some of them are convinced of relaxation.another group says that masalik arbaa is a much later production. Ther was no such concept during the time of the companions of the prophet and the tabieen, but people used to go to the scholar of intercession.and they use to accept there fatwa and next time they would go to another scholar for intercession. Companions of rasool(SAW) and tabieen did not solve problems by religious grouping.this issue is controversial among the scholar of islam, hence the researcher want to present the opinion of scholars in a rsearch style.